Do nurses or doctors have an increased risk of developing multiple sclerosis?. Issue 10 (October 1990) - Dean, G; Gray, R
Abstract : A cluster of multiple sclerosis (MS) patients has been reported in seven of 307 nurses in Key West, Florida. The MS death rates in British nurses and qualified medical practitioners were looked at and no increased mortality from multiple sclerosis was found. Neither was there an increase in mortality from motor neuron disease (amyotrophic lateral sclerosis), the control disease. Death rates from MS vary with social class, being highest in social class IIIN (skilled non-manual) and lowest in social class II (intermediate). These different rates may be due to MS causing health related occupational mobility. Allowance for the inter-class variability in MS death rates did not materially affect the conclusion that death from MS appears to be no more common than expected among nurses and doctors than in the general population. Possible explanations for the cluster of multiple sclerosis among nurses in Key West are discussed.